Pro-Kontra Kewenangan Mahkamah Konstitusi dalam Menguji Undang-Undang yang Mengatur Eksistensinya - Lailam, Tanto (Jurnal Konstitusi, 2015)
The Pro’s – Con’s of the Constitutional Court in the review of law in a regulated of the authority, since, it was a conflicting of procedural principles between “ius curia novit” with “nemo judex idoneus in propria causa”. Morever, the background by implication of Constitutional Court decisions, sometimes Constitutional Court making a “rule breaking”,  for examples: nullify of some of law if had reduction of  the authority, addition of constitutional authority to review of law before the 1945 Constitution amendment, additional authority to review of Government Regulation in lieu of law, and used non-constitution as a standard in the formal review, and others. On the other hand, the Constitutional Court also sometimes to choose a   legal logic doesn’t precise and anti-accountability principle. The Conflicts of the procedural principles can  be  resolved  by  understanding  philosophy  of  purposes of law (justice value, legal certainly, utility principle), so that, the Court will have been prioritizing to “ius curia novit” principle and it ignored “nemo judex idoneus  in propria causa”principle, it is intended that the enforcement of the constitution (values) and the state of the Indonesian rule of law, as well as for the Court to aims decided of constitutional issues and to aim the protection of constitutional rights.